1988
DOI: 10.1128/mcb.8.8.3191
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor induction by the adenovirus type 5 E1A 12S protein is required for immortalization of primary epithelial cells.

Abstract: The 12S protein encoded by the adenovirus EIA region induces cellular DNA synthesis in and proliferation and immortalization of primary rat epithelial cells in the presence or absence of serum. It also induces the production of a growth factor(s) that stimulates epithelial cell proliferation. We have undertaken a mutational analysis of the 12S gene to determine the sequences required for these functions. We found that a region near the C-terminus of the 12S protein was required for growth factor induction. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In contrast, other experiments have provided evidence for a role for these sequences in the immortalizing function of E1A as well as to collaborate with adenovirus E1B in transformation (31). Although the basis for the apparent discrepancy in these results is unclear, the latter findings, indicating a requirement for the C-terminal domain in E1A function in immortalization and transformation with E1B, are certainly consistent with the findings that this domain interacts with CtBP and thus would disrupt the formation of the E2F-p130-CtIP-CtBP repressor complex.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, other experiments have provided evidence for a role for these sequences in the immortalizing function of E1A as well as to collaborate with adenovirus E1B in transformation (31). Although the basis for the apparent discrepancy in these results is unclear, the latter findings, indicating a requirement for the C-terminal domain in E1A function in immortalization and transformation with E1B, are certainly consistent with the findings that this domain interacts with CtBP and thus would disrupt the formation of the E2F-p130-CtIP-CtBP repressor complex.…”
Section: Discussionmentioning
confidence: 91%
“…The cells (WTras+WTrac) derived from primary epithelial cells that express only WT12S and the endogenous, WTras and rac are immortalized and not transformed (they cannot grow in soft agar or form tumors in animals). They resemble the original primary cells in appearance and expression of epithelial characteristics (Quinlan et al, 1988;Quinlan and Douglas, 1992;Gopalakrishnan and Quinlan, 1995;Fischer and Quinlan, 1998a) and see below.…”
Section: Resultsmentioning
confidence: 99%
“…Primary BRK cells were prepared from 5 day-old rats (Fisher F344, Harlan, IN, U.S.A.) as described previously (Quinlan et al, 1988). The cell lines have been described previously (Fischer et al, 1998).…”
Section: Cell Culture and Growth Assaysmentioning
confidence: 99%
“…The Drosophila melanogaster homologue dCtBP mediates transcriptional repression by at least six different transcription factors, including Knirps, Kruppel, Snail, Zfh-1, Polycomb, and Hairy (16,17,20,22,28). CtBP also interacts with Xenopus and human Polycomb proteins (28), and human hCtBP acts as a corepressor for the ZEB transcription factor that is involved in the regulation of lymphocyte and muscle differentiation (23). The mouse homologue mCtBP is a corepressor for the NET member of the Ets family of transcription factors and oncogenes (3).…”
mentioning
confidence: 99%
“…Although the precise significance of this interaction remains unknown, it is essential for the immortalization of primary rodent cells by E1A and has also been reported to negatively modulate E1A-mediated transformation, tumorigenicity, and metastasis (2,23,24,27,29). More recently it has been shown that this E1A-binding protein is one of a highly conserved family of (co)repressors of transcription.…”
mentioning
confidence: 99%